Climate Change Refugees in Indonesia: Human Rights Protection amid Legal Vacuums and UNHCR Single Submission - Octaviani, Rury; Syahrin, M. Alvi; Becanics, Adrienn; Rahmah, Shafiyah (Lampung Journal of International Law, 2025)
Climate change has become a major driver of cross-border displacement, creating the phenomenon of climate refugees. Although the 1951 Refugee Convention does not explicitly recognize this category, the reality of climate-induced displacement demands legal and policy responses from states, including Indonesia. As a transit country, Indonesia lacks a national legal framework specifically addressing the status and protection of climate refugees, and in practice, protection relies on the United Nations High Commissioner for Refugees through the single submission scheme, the only system for refugee identification and registration in the country. This reliance exposes a regulatory vacuum and legal vulnerabilities related to state sovereignty. This paper examines Indonesia’s response, highlighting the importance of updating national regulations and strengthening coordination with UNHCR to provide inclusive, human rights-based protection for climate refugees.